Exploring the prospects for professional development of postgraduate supervisors at the National University of Lesotho - Tebello Violet Tlali (University of Johannesburg, 2023)
The higher education developments are gradually enabling the re-conceptualisation of postgraduate research supervision as a teaching and learning practice. This re-conceptualisation has also led to the recognition that postgraduate research supervisors need to be appropriately capacitated so that they can master the supervisory craft. This study sought to explore the prospects for professional development of postgraduate supervisors at the National University of Lesotho, by examining supervisor's experiences in their trajectories in learning how to become supervisors and to identify their further professional development. Fifteen supervisors took part in the study. Nine (three associate professors and six senior lecturers) were interviewed through semi-structured interviews while six junior lecturers were interviewed through a focus group interview. The findings revealed that while most supervisors relied mainly on the way they were supervised, they also value the experiential learning accrued in their trajectories as supervisors. Hence the study highlights issues for consideration in advancing professional development of postgraduate supervisors at the National University of Lesotho